HUBUNGAN MASA KERJA, TINGKAT KECEMASAN, PENGGUNAAN MASKER DAN PAPARAN BAHAN ROKOK TERHADAP GANGGUAN SIKLUS MENSTRUASI KARYAWAN WANITA PABRIK ROKOK DI LAMONGAN - Indartik Mamnuah; Sri Winarni; Dharminto Dharminto; Farid Agusyahbana (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Irregular menstruation is an unbalanced process of hormones in the female reproductive system in which between the hormones estrogen and progesterone. Based on preliminary study 80% female employees of cigarette factory suffered from menstrual problems with 37.5% Amenorrhea, 37.5% oligomenorrhoea and 25.0% polimenorea.Objectives: This study aims to determine the relationship of Work Period, Level of Anxiety, The Use of Masks and Exposure of Cigarettes Against Menstrual Cycle Disorders of Women Employees of Lamongan Cigarette Factory. Method: This research type is explanatory research with cross sectional study design. The study population was 500 female employees and the sample used was 84 female employees with Simple Random Sampling technique. Data analysis included univariate analysis, descriptive bivariate analysis (crosstab), analytic bivariate using chi square Yates Correction and Point Biserial Correlation. Result: The analysis of the study showed that there was no significant relationship between work period (P-value = 0.334), anxiety level (P-value = 0.469), Mask use (P-value = 0.567), cigarette exposure (P-value = 0.280) with menstrual cycle disorders. Conclusions: The conclusion of this study is that there is no relationshipbetween work period, anxiety level, mask use and cigarette exposure with menstrual cycle disorders. Suggestions that can be given is the need for regular health checks to check the health status of employees.